German's business engineering is now in Malaysia - Lee, Khai Loon (2019)
Business Engineering is a new branch in the business field and the programme is available at Universiti Malaysia Pahang (UMP). Graduates of this programme will become the frontrunners in business engineering of which they will integrate knowledge and skill by transforming business practices with innovative practices. They can be specialists in logistics, chain supply and production.